Impact of Concomitant Grade I Degenerative Spondylolisthesis on Clinical and Radiographic Outcomes Following Biportal Endoscopic versus Microscopic Laminectomy for Lumbar Spinal Stenosis: A Post Hoc Analysis of a Multicenter Randomized Clinical Trial - Hyun-Jin Park; Min-Seok Kang; Kwang-Sup Song; Dae-Woong Ham; Ho-Joong Kim; Ki-Han You; Seung-Yeon Jeong; Jin-Sung Kim; Sang-Min Park (Global Spine Journal, 2026)
Study Design Post hoc analysis. Objective To determine whether Meyerding grade I degenerative spondylolisthesis (DS1) modifies 12-month clinical or radiographic outcomes after biportal endoscopic laminectomy (BE-L) versus microscopic laminectomy (M-L) for lumbar spinal stenosis, and to compare the two techniques among patients with DS1. Methods Of 120 randomized ENDO-BS participants, 101 who underwent single-level decompression with classifiable spondylolisthesis status were analyzed (BE-L, n=49; M-L, n=52) and stratified by DS1 status. Outcomes were assessed preoperatively, at 2 weeks, and at 3, 6, and 12 months. Linear mixed-effects models tested group × time interactions within each arm and between techniques among patients with DS1. Results All patient-reported outcomes improved significantly from baseline to 12 months in every subgroup, and no DS1 × time interaction reached significance in either arm. Among patients with DS1, no significant between-technique difference or technique × time interaction was detected for any clinical outcome. Slip percentage and the instability ratio (flexion–extension angular motion) increased modestly over time in both arms, but no radiographic parameter differed significantly between techniques. Complication rates did not differ by DS1 status. Conclusion In this exploratory analysis, concomitant Meyerding DS1 was not associated with significantly different 12-month outcomes after BE-L or M-L. Among patients with stable DS1, no significant differences between techniques were detected; slip percentage and the instability ratio increased modestly in both arms. Longer follow-up is required to clarify the late significance of this progression.